The captives are translated, attached at the wrists' : a study of Antillean identities in the works of Édouard Glissant, Maryse Condé and Patrick Chamoiseau - Wawn, Amy (French Language and Literature, 2014)
This thesis presents a study of the various interpretations of Creole identities in the French Caribbean, with reference to the literary works of three esteemed French Creole authors, namely, Édouard Glissant, Maryse Condé and Patrick Chamoiseau. Due to the horrific nature of the transatlantic slave trade as well as the arrogance of former colonising nations, the true 'voice' of the slaves and their descendants ? the foundation of Creole societies ? has been largely silenced in the official archives of France, and threatens to disappear irretrievably. The Creole authors I discuss attempt to combat these silences through a rewriting and recreation of history through literature. As a tool in analysing the ways in which these authors have interpreted the silencing and fragmentation of their histories, I present and discuss the metaphor of the transatlantic slave trade as an act of physical and metaphorical translation. More specifically, I suggest that the Middle Passage can be seen as the translation of human bodies and identities from East to West across the Atlantic Ocean, from their origins in the continent of Africa, to the Americas and to the islands of the Antilles. Secondly, I propose that a human being can be compared to a living, literary text that contains a wealth of cultural information, language and history, a text that can be subjected to translation. In order for this metaphor be complete, I introduce a possible translator in the vast system of the transatlantic slave trade, a professional that played a major role in the translation of African captives into 'slave bodies' for France. To demonstrate how these Creole authors have interpreted their past, I discuss selected theories on the translation of a literary text and compare them to the metaphorical and literal translation of a human being. I argue that the various ways in which the literary text resists or complies to a translation into another language may reveal insights into how the transatlantic slave reacted to his own translation into slavery. Secondly, I suggest that the slave's resistance towards hisor her translation into slavery may be seen to represent the resistance that Creole oral tradition displays towards a translation into the strictly linear nature of Western, written narratives. Finally, I conclude that translation can be seen as an act of resistance in itself. In translating their histories from oral tradition, myth and legend into written narrative and specifically into French literature, Creole authors display a resistance to the silencing of their histories in the oppressive narratives of the coloniser. Their literary works can thus be seen as alternative, 'conceptual' narratives that challenge the dominant, often oppressive narratives of our time.